Fresno County Bar Association Luncheon: State Bar President David Heilbron Speaker - Watkins, Howard::::::::: (1986)
Judge Robert Coyle, State Bar Board Public Member Glee Ewell, District 5 Governor Dennis Cornell and David Heilbron Speech title "Is There Life After Sacramento?"